Antibacterial activities of Elaeocarpus ganitrus Roxb. leaves from Kebumen against Escherichia coli and Shigella flexneri - Naelaz Zukhruf Wakhidatul Kiromah; Laeli Fitriyati; Sinta Wahyu Septiani (Universitas Ahmad Dahlan, 2023)
Ganitri (Elaeocarpus ganitrus Roxb) is a plant known for its antibacterial properties, particularly in its leaves. The leaves of Ganitri contain antibacterial compounds such as flavonoids, alkaloids, and tannins. The objective of this study is to investigate the antibacterial activity and determine the minimum concentration of ethanol, methanol, and distilled water extracts from Ganitri leaves in inhibiting the growth of Escherichia coli and Shigella flexneri bacteria. A preliminary study of phytochemical with Thin Layer Chromatogram (TLC) and antibacterial study was conducted. The study was conducted in vitro by disc diffusion method with positive control of ciprofloxacin 50 µg/mL and negative control of sterile aquadest. The extract concentration series used were 10, 20, 30, 40, 50, and 100%. The extracts of ganitri leaves have antibacterial activities against Escherichia coli and Shigella flexneri bacteria. The TLC results were observed under visible light at 254 and 365 nm. Ethanol, methanol, and aquadest extracts of ganitri leaves produce spots that are almost comparable to the compounds of quercetin and tannic acid. The inhibitory zone range of the extracts in Escherichia coli bacteria is 10.33-19.66 mm with a strong category. In comparison, the inhibitory zone range of Shigella flexneri is 8.88-22.62 mm with a moderate-very strong category. ANOVA test results stated a significance value of p = 0.001 (p <0.05). Therefore, it can be concluded that the ethanol, methanol, and aquadest extracts of ganitri leaves had significant differences. The minimum concentration of each extract in inhibiting the bacteria Escherichia coli and Shigella flexneri is 10%.